Forged : writing in the name of God : why the Bible's authors are not who we think they are - Ehrman, Bart D. (New York : HarperOne, 2011)
"In FORGED New York Times bestselling author, Bart Ehrman, reveals another hidden scandal of the Bible. For centuries, scholars have known that not all of the books in the New Testament are authentic while the general public has been blissfully unaware. The books of the New Testament are widely assumed to be written accounts of Jesus's life by those who knew him best. However, if the Gospels and letters were not written by memebers of Jesus's inner circle--but by later writers with differing agendas in rival communitites--then the authority of the Bible collapses. Based on new, original research, Ehrman takes the reader on a journey to the ancient world and the forgery battles that raged throughout the Roman Empire. The popular myth is that "writing in the name of another" was a common, accepted practice in antiquity. Not so argues Ehrman. Forgery was as scandalous then as it is now. And yet, at a time when all documents and letters where copied by hand and circulated freely with little or no authorial control, identifying who actually penned a piece of writing-be it political, historical, or religious-was fraught with uncertainty. FORGED exposes the forged letters written in the name of Jesus's disciples for the expressed purpose of gaining acceptance in the early church...which is exactly what happened and why we have the Bible we read today"--
Includes bibliographical references (p. [267]-291) and index.
Keywords: Bible. -- Authorship; Bible. -- Controversial literature; Bible. -- Evidences, authority, etc; Bible. -- Criticism, interpretation, etc